2021
DOI: 10.1080/23744235.2021.1884745
|View full text |Cite
|
Sign up to set email alerts
|

Lombardy, Northern Italy: COVID-19 second wave less severe and deadly than the first? A preliminary investigation

Abstract: The much-heralded second wave of coronavirus disease has arrived in Italy. Right now, one of the main questions about COVID-19 in Italy is whether the second wave will be less severe than the rst.Currently, the answer to this question remains open.According to the Italian Ministry of Health website (COVID-19 -Situation in Italy), it would appear that in Italy the COVID-19 second wave is less severe and deadly than the rst one was.However, this difference could be affected by several factors, including the dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…In our study, the second COVID-19 wave was less deadly and had a slower rise and lower peak compared to the first wave. While this finding is in line with COVID-19 resurgences observed in other parts of the world [ 8 , 9 , 28 , 29 ], many countries experience a more traditional pattern. For example, COVID-19 resurgences are reportedly much worse in India, Taiwan, Turkey and other countries ( https://graphics.reuters.com/world-coronavirus-tracker-and-maps/ ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, the second COVID-19 wave was less deadly and had a slower rise and lower peak compared to the first wave. While this finding is in line with COVID-19 resurgences observed in other parts of the world [ 8 , 9 , 28 , 29 ], many countries experience a more traditional pattern. For example, COVID-19 resurgences are reportedly much worse in India, Taiwan, Turkey and other countries ( https://graphics.reuters.com/world-coronavirus-tracker-and-maps/ ).…”
Section: Discussionsupporting
confidence: 84%
“…Despite many measures to combat COVID-19, multiple resurgences are occurring around the world [8] , [9] , [10] , [11] , reflecting variable successes in controlling SARS-CoV-2 infection. Because future resurgences of this virus and its variants are likely, it is crucial to understand how this affects disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the work by Bongiovanni et al 1 , who by comparing patients admitted to emergency room of ASST Rhodense, in Lombardy region, during the first wave (2-8 March 2020) and the second wave (19-25 October 2020), concluded that "the severity and the mortality of COVID-19 infection was lower during the 2 nd wave of pandemic". Their findings confirm those found in a similar research by Borghesi et al, in Lombardy region 2 . Despite both these studies have similar relevant limitations, which are the lack of comparison with the final outcome, since the studies were carried out at the beginning of the COVID-19 second wave, and the fact that a "relatively small number of cases is not sufficiently representative of such a large target population" 2 , they are well representative of the situation in Lombardy region, where official figures show 16,362 deaths (47.7% of all deaths in Italy) during the first wave (March-May 2020) and 15.515 deaths (18.9% of all the deaths in Italy) during the second and the third wave together 3 .…”
supporting
confidence: 93%
“…More recently published clinical trials reported mortality rates between 5.1 and 10.4%, but included patients were recruited as late as July 2020 and mean age was considerably lower (55 years) [15,16]. Data on COVID-19 pneumonia mortality during the second wave are lacking and the scarce available information suggests that mortality rates have declined, at least in developed countries, but this observation could be explained by the fact that second-wave infections tended to affect younger people and it cannot be attributed with certainty to therapeutic advances [17][18][19]. Another plausible explanation is provided by Asch and colleagues, who found that the risk-adjusted mortality decreased from 16.56% to 9.29% in the early period of their study (January through April 2020) compared with the later period (May through June 2020), reflecting a possible association between an increased in-hospital mortality and a high prevalence of COVID-19 in the community [20].…”
Section: Mortality and Comparison With Other Seriesmentioning
confidence: 99%